Differentiation of mouse fetal lung alveolar progenitors in serum-free organotypic cultures - Konstantinos Gkatzis (eLife Sciences Publications Ltd, 2021)
Lung epithelial progenitors differentiate into alveolar type 1 (AT1) and type 2 (AT2) cells. These cells form the air-blood interface and secrete surfactant, respectively, and are essential for lung maturation and function. Current protocols to derive and culture alveolar cells do not faithfully recapitulate the architecture of the distal lung, which influences cell fate patterns in vivo. Here, we report serum-free conditions that allow for growth and differentiation of mouse distal lung epithelial progenitors. We find that Collagen I promotes the differentiation of flattened, polarized AT1 cells. Using these organoids, we performed a chemical screen to investigate WNT signaling in epithelial differentiation. We identify an association between Casein Kinase activity and maintenance of an AT2 expression signature; Casein Kinase inhibition leads to an increase in AT1/progenitor cell ratio. These organoids provide a simplified model of alveolar differentiation and constitute a scalable screening platform to identify and analyze cell differentiation mechanisms.